Monitoring of blood glucose levels in a cat with diabetes mellitus: a case report - Ajeng Dwi Kusuma; Latania Ghina Dhikriyanti; Indahsari Nur Rochmawati; Sus Derthi Widhyari; Aryani Sismin Satyaningtijas (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2026)
Background Diabetes mellitus (DM) is a chronic metabolic disorder in cats characterized by persistent hyperglycemia resulting from impaired insulin secretion, insulin resistance, or both, and is not always accompanied by pancreatic or hepatic dysfunction. Objective This case study aimed to describe the clinical findings and therapeutic management of a cat diagnosed with diabetes mellitus with suspected hepatic and pancreatic dysfunction. Case An 11-year-old female domestic cat named Miau Miau was presented to the Waras Satwa Veterinary Clinic, Batam, Indonesia, with diarrhea, decreased appetite, polyuria, and polydipsia. Examination The diagnostic approach included anamnesis, physical examination, hematological evaluation, blood biochemistry analysis, and serial blood glucose monitoring using a glucometer. Persistent hyperglycemia was established based on repeated blood glucose values above the normal range (75–120 mg/dL) during the observation period. The findings revealed hyperglycemia (318 mg/dL) with increased levels of amylase, alanine aminotransferase (ALT), and total bilirubin, indicating possible involvement of the pancreas and liver. Diagnosis and treatments The cat was diagnosed with diabetes mellitus with suspected hepatic and pancreatic dysfunction. The treatment included Moringa leaf (Moringa oleifera) as an adjunct therapy in oral capsule form at a dose of ±98 mg/kg body weight/day, combined with pancreatic enzyme supplementation, a hepatoprotective agent, and dietary modification to a high-protein, low-carbohydrate diet. After 14 days of hospitalization, the blood glucose levels gradually decreased to 115 mg/dL. Conclusion This case demonstrates that diabetes mellitus in cats may be associated with pancreatic and hepatic dysfunction, as reflected by increased levels of amylase, ALT, and total bilirubin.